2021
DOI: 10.47836/ifrj.28.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Reducing microbial contamination risk and improving physical properties of plant-based mayonnaise produced using chickpea aquafaba

Abstract: Aquafaba is obtained by soaking different types of legumes, and utilised in the production of several plant-based foods due to its functional properties. The present work aimed to evaluate the effects of aquafaba produced by soaking chickpeas at different durations, on the safety, physicochemical properties, and consumer acceptability of plant-based mayonnaise. The chickpea aquafaba was prepared by soaking chickpea at different durations of 12, 18, and 24 h, and later boiled for 35 min at 120°C. The results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The total soluble solids (TSS) and the total solids of the CA in the present work were 6.3 ± 0.2 °Bx and 5.7 ± 0.2%, respectively. In the study carried out by [ 29 ], the TSS content of the CA varied from 5.09–5.89 °Bx, and the authors reported a direct relation between the increase in soaking time and TSS, because of the accumulation of the water-soluble materials in the aquafaba. A longer cooking time increased the leakage of the water-soluble elements and pigments, which in turn manifested on the overall color of the CA [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The total soluble solids (TSS) and the total solids of the CA in the present work were 6.3 ± 0.2 °Bx and 5.7 ± 0.2%, respectively. In the study carried out by [ 29 ], the TSS content of the CA varied from 5.09–5.89 °Bx, and the authors reported a direct relation between the increase in soaking time and TSS, because of the accumulation of the water-soluble materials in the aquafaba. A longer cooking time increased the leakage of the water-soluble elements and pigments, which in turn manifested on the overall color of the CA [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the category of products that include brioche, spray-dried legume aquafaba was used as a foaming agent [22,[84][85][86][87]. The specific volume of these brioche was lower compared to egg-based muffins [88], but the results regarding the mass loss during baking showed much lower values for aquafaba muffins compared to the control sample.…”
Section: Possibilities Of Using Aquafaba In the Production Of Food Pr...mentioning
confidence: 99%
“…Table mayonnaise sauces have a creamy consistency and are intended for consumption as seasonings or additives for cooking at home and in public and restaurant businesses. Mayonnaise sauces are universal products that reduce the caloric content of food by replacing some recipe ingredients with low-calorie ones, for instance, replacing sugar with sweeteners [2].…”
Section: Introductionmentioning
confidence: 99%